(untitled) («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
This article discusses the concept lacunae in linguistics and modern lacunarism in translation and its problems, especially in Uzbek language.